Effect of Scaffolding Instructional Strategy on Performance in Ecology Concepts among Secondary School Students in Gumel, Jigawa State, Nigeria (Federal University Gusau Faculty of Education Journal, 2025)
This study investigated the effects of Scaffolding Instructional Strategy on performance in Ecology concept among secondary school students in Gumel Education Zone, Jigawa State, Nigeria. The study adopts a Quasi-Experimental Design, particularly the pretest, posttest, quasi-experimental and control group design. The population comprised all 3239 SS2 Biology students from 17 public Senior Secondary Schools in Gumel Education Zone. A sample of 124 students from two randomly selected out 4 co-educational schools was used for the study. The study involves two groups experimental and control. The experimental group was taught Ecology concept using Scaffolding Instructional Strategy while the Control Group was exposed to the same concept using lecture Method. One instrument were used for data collection, namely, Ecology Performance Test (EPT). The instrument were validated by experts in Ahmadu Bello University, Zaria and have reliability coefficients of 0.88 and estimated using Pearson Product Moment Correlation (PPMC). Two research objectives, two research questions and two null hypotheses were formulated to guide this study. Research questions were answered using Mean and Standard Deviation, while null hypotheses were tested using Independent Sample t-test at 0.05 level of significance. The major findings revealed a significant difference between the mean scores of experimental and control groups in their performance, in favour of the experimental group. It is therefore recommended among others that secondary school Biology teachers should frequently employ Scaffolding Instructional Strategy in teaching difficult and abstract concepts in Biology like Ecology